Fistula Eligibility: A Work in Progress. Issue 2 (5th February 2014) - Al‐Jaishi, Ahmed A.; Moist, Louise M.
Abstract Effective hemodialysis requires a reliable vascular access. Clinical practice guidelines strongly recommend the fistula as the preferred option followed by arteriovenous (AV) grafts, with central venous catheters being least preferred. Recently, there has been a growing awareness of the limitations of the fistula, its high rate of primary failure and that a fistula may not be appropriate for all patients initiating or on hemodialysis. However, determinates for fistula eligibility have not been clearly defined. The creation and use of a fistula requires the complex integration of patient, biological, and surgical factors, none of which can be easily predicted or planned. There have been several successful initiatives over the last decade addressing patient suitability for AV access, but none have validated defined criteria for fistula eligibility. We discuss these initiatives by addressing: 1) process of care, 2) radiological and nonradiological tests and procedures, and 3) alternative surgical approaches. Careful clinical judgment, appropriate vascular access assessment and placement, and an individualized approach to the risks and benefits will optimize patient health outcomes while minimizing prolonged catheter dependence among hemodialysis patients.